2018
DOI: 10.1186/s12888-018-1611-4
|View full text |Cite
|
Sign up to set email alerts
|

Does Chinese calligraphy therapy reduce neuropsychiatric symptoms: a systematic review and meta-analysis

Abstract: BackgroundThere are currently no systematic reviews or meta-analyses of Chinese calligraphy therapy (CCT) to reduce neuropsychiatric symptoms. The aim of this systematic review and meta-analysis was to explore the efficacy of CCT for people with neuropsychiatric symptoms.MethodsWe searched Chinese and English databases, including the Cochrane Central Register of Controlled Trials and Wanfang Data for relevant articles published between the earliest year available and December 2016. The search was limited to ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 14 publications
2
23
0
Order By: Relevance
“…Although the current treatment for anxiety (and mental disorder in general) is the consolidated drug–psychotherapy approach, its consequences include adverse effects of drugs, lack of response to treatment, high cost of psychotherapy, or/and pharmacological interventions. [ 3 4 5 ] Therefore, the need for effective low-cost strategies has become increasingly urgent and necessary because they might provide the individuals with the right tools to cope with anxiety while changing lifestyle and reducing the economic cost.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the current treatment for anxiety (and mental disorder in general) is the consolidated drug–psychotherapy approach, its consequences include adverse effects of drugs, lack of response to treatment, high cost of psychotherapy, or/and pharmacological interventions. [ 3 4 5 ] Therefore, the need for effective low-cost strategies has become increasingly urgent and necessary because they might provide the individuals with the right tools to cope with anxiety while changing lifestyle and reducing the economic cost.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, both health professionals and patients agree on two points: (1) it is not satisfactory to spend an entire lifetime making use of drugs and (2) traditional psychotherapy can be extremely costly if carried out for long periods. In addition, clinical trials have demonstrated that anxiolytic drugs and antidepressants have limited effectiveness,[ 3 ] cause dependence,[ 4 ] affect cognition and memory,[ 4 5 ] and cause sexual dysfunction. [ 5 ]…”
Section: Introductionmentioning
confidence: 99%
“…In addition, other clinical areas of CCH treatment include (1) Chinese cancer (nasopharyngeal carcinoma) patients with CCH training who demonstrated gradually lowered systolic blood pressure and respiration rate at pre-and posttreatment measures as the intervention proceeded, as well as elevated level of concentration and reduced mood disturbance (Yang, Li, Hong, & Kao, 2010); (2) our CCH training of post-earthquake PTSD children, which led to significant decrease in hyperarousal symptoms and salivary cortisol levels among the child survivors (Zhu et al, 2014); and (3) that CCH training plus Wenlafaxine drugs, which yielded better effects in treating patients of anxiety disorder that were measured by the Hamilton Anxiety Scale (HAMA), Self-Rating Anxiety Scale (SAS), and Clinical Global Impression (CGI) Scale (Dong, Jia, Wang, Cui, & Zhang, 2006). These results provide encouraging evidence on the strength of CCH intervention toward reducing certain neuropsychiatric symptoms and conditions (Chu, Huang, & Ouyang, 2018;Wagner, 2018).…”
Section: The Applicationsmentioning
confidence: 68%
“…Because calligraphy is written with a brush as the main tool, it requires a place and a relatively quiet environment, together with a longer intervention program that takes about 45 to 60 minutes including preparation work (Kao et al, 1984). To apply as a clinical trial in the future, a design of different graphic characters to target specific neuropsychiatric diseases (Chu, Huang, & Ouyang, 2018) with 30 to 45 minutes intensive treatment is required for calligraphy and Guqin finger writing.…”
Section: Resultsmentioning
confidence: 99%
“…Chinese calligraphy, the art of Chinese characters written with a soft brush, is widely regarded as a unique form of art (Kao et al, 2014;Kao, 2010;Chu, Huang, & Ouyang, 2018). Calligraphy originated early and has various forms.…”
Section: Literature Reviewmentioning
confidence: 99%